Knowledge, attitudes, and willingness of bipolar disorder patients toward electroconvulsive therapy: a cross-sectional study - Zhou, Lin; Qi, Xinmeng; Xu, Liuliu; Duanmu, Xinrong; Wang, Ke; Liu, Kai; Zhang, Yue (Frontiers in Public Health, 2025)
ObjectiveThis research aims to explore the levels of knowledge, attitudes, and willingness (KAW) of patients with bipolar disorder (BD) regarding electroconvulsive therapy (ECT).MethodsA cross-sectional survey was conducted in Nanjing from April 10 to November 3, 2024, using a validated questionnaire [Cronbach's α = 0.936, Kaiser–Meyer–Olkin (KMO) = 0.917]. Participants completed structured items assessing knowledge, attitudes, and willingness toward ECT. Data analysis involved descriptive statistics, non-parametric tests, Spearman correlation, multivariate logistic regression, and structural equation modeling (SEM).ResultsThe study successfully enrolled 479 participants. Of these, 282 participants (58.87%) were female. One hundred and sixty seven respondents (34.86%) had previously undergone ECT. The mean knowledge, attitude, and willingness scores were 5.57 ± 4.84 (possible range: 0–16), 29.08 ± 6.21 (possible range: 9–45), and 21.49 ± 5.14 (possible range: 6–30), respectively. SEM analysis showed that electroconvulsive therapy (β = −0.377, P = 0.014), years of BD (β = 0.196, P = 0.014) had direct effects on knowledge. Knowledge (β = 0.526, P = 0.023) directly affected attitude. Meanwhile, electroconvulsive therapy (β = −0.198, P = 0.013) and years of BD (β = 0.103, P = 0.016) indirectly affected attitude. Knowledge (β = 0.107, P = 0.018), attitude (β = 0.674, P = 0.009), and gender (β = 0.104, P = 0.020) directly affected willingness. Knowledge (β = 0.355, P = 0.011), electroconvulsive therapy (β = −0.174, P = 0.015), and years of BD (β = 0.090, P = 0.020) indirectly affected willingness.ConclusionThe study found that bipolar disorder patients generally lack knowledge and hold negative attitudes but demonstrate a relatively high willingness to accept ECT treatment. Targeted educational programs are recommended to improve understanding, shift attitudes, and enhance acceptance of this treatment in clinical willingness.